(untitled) (MAUSAM, 1968)
The summary of a transient analysis of cup anemometer is presented. It is shown that the steady state calibration curve and the transient characteristics of anemometers can be calculated purely from the theoretical condsideration using the raw data on the inertia, static aerodynamic forces on the cups, minimum wind speed at which the practical anemometer begins to rotate and any particular value of observed speed of rotation in the middle of the range of operation. The calculated characteristics are shown to agree with the published experimental data for the British cup generator anemometer.